Confusing Quantitative Descriptions of BrønstedLowry AcidBase Equilibria in Chemistry Textbooks – A Critical Review and Clarifications for Chemical Educators. Issue 1 (January 2014) - Meister, Erich C.; Willeke, Martin; Angst, Werner; Togni, Antonio; Walde, Peter
Abstract In chemistry textbooks, the pK<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40b37zmn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> a, H 2O</alternatives> value of water in the solvent water at 25 °C is sometimes given as 14.0, sometimes as 15.7. This is confusing. The particular chemical reaction considered is the one in which water as BrønstedLowry acid reacts with water as BrønstedLowry base in water as solvent to yield equal concentrations of hydrated oxonium and hydroxide ions, H3O+(aq) and HO−(aq), respectively. This reaction is also known as the 'self‐ionization' of water for which the equilibrium constant is abbreviated as Kw with its known value of 10−14.0 at 25 °C, i.e., pKw(25 °C)=14.0. Identical values for pK<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40b37zdb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> a, H 2O</alternatives> and pKw at a fixed temperature appear reasonable, since K<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40b37zgf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> a, H 2O</alternatives> and Kw refer to one and the same reaction. Therefore, reasons for the apparent disagreement between the 'thermodynamically correct' pKa value for water (14.0 at 25 °C) and the value reported in most organic chemistry textbooks (15.7) should be discussed when teaching acidbase chemistry. There are good arguments for introducing, from the very beginning, the concepts of activity and thermodynamic standard states when teaching quantitative aspects of chemical equilibria. This also explains in a straightforward way why all thermodynamic equilibrium constants, including Kw, are dimensionless, and why pK<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40b37zk3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> H 3O +</alternatives>(25 °C)=0.